Re-ranking Olympic performances: Are Morocco's medals a greater accomplishment than the US's many medals? - Myers, A.; Kalet-Schwartz, S.; Wai, J. (MAR - Muhlenberg Academic Review, 2021)
This paper, first, evaluates the factors that influence the medal count at the Olympic Games, using the 2016 Rio Olympics medal count data for the analysis. The paper identifies and models a few socioeconomic variables that influence a country`s medal tally, including HDI, GDP per Capita, Population, whether or not the country hosted, and previous Olympic medal count. Second, the paper evaluates each country`s actual performance to the model`s expected performance. We subtracted the model`s output from the Olympic data and ranked them by the size of their residual. While traditional rankings compare each country by their total number of medals, this analysis ranks countries by how much they exceeded their model`s expected performance. This method allows countries to be compared on more equal grounds. The results indicate that population size and previous Olympic medal tally significantly impact a country`s medal count. Furthermore, the results reveal that many countries that did not rank high on traditional ranking systems outperformed their expected medal count and ranked higher on our new ranking system than top medal winners. This study emphasizes the need to consider the impact of socioeconomic factors on Olympic medal tallies.